JIHADIS TERORISME: TITIK TEMU ANTARA AGAMA DAN KEKERASAN - Majid, Abdul; Zainab, Cut (Al-Ijtima`i: International Journal of Government and Social Science, 2021)
Lately, there have been many incidents that have shocked the public, one of which is the bombing that occurred in Makassar under the guise of jihad fisabilillah. Many people are scared, non-Muslims become anxious, because they are scared if they become targets of terrorism. The violence that often occurs is an interesting topic to discuss together. Is it true what the jihadis say that is Religion that promotes this act of terrorism? In fact, if we look at religious values, there is no religion that teaches violence, no religion teaches killing fellow human beings. Moreover, the religion of Islam which loves peace and teaches love and compassion to all corners of the universe. However, if religion is not the real background, then what? Politics, transfer of issues and others. Many have misunderstood the interpretation of this jihad verse which has led to a misunderstanding of the teachings of jihadis terorisme. They think that this all-sophisticated and modern world is wrong, therefore they want to uphold the 'kedaulatan Allah' or what is commonly called the Islamic world which is ruled by the Khalifah which is actually no longer possible in this democratic country. This is a challenge for us to continue to study and deepen the science of religion properly so as not to be influenced by the teachings of the Jihadis terorisme.